2021
DOI: 10.4067/s0034-98872021000901352
|View full text |Cite
|
Sign up to set email alerts
|

When it is time to decide: factors associated to the choice of a medical specialty

Abstract: After finishing their initial education, physicians can enter post-graduate training programs. In Chile, there are multiple medical specialties options. This review synthesizes the factors associated with the choice of specialty, according to international publications. Students coming from rural areas or small towns would tend to choose Family Medicine. Men prefer specialties such as Surgery. Having relatives in the medical profession, specializing in a specific field, also influence the choice. Concerning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Medical students’ specialty choice is influenced by a number of factors. Traditionally, interests and preferences, personal traits, sociodemographic factors, and learning experiences are known to be important [ 7 ]. A change has taken place in recent decades among medical students to follow specialties that offer greater control over lifestyle, and the less flexible lifestyle of surgical specialties has become an important reason for viewing this field as less attractive [ 7 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medical students’ specialty choice is influenced by a number of factors. Traditionally, interests and preferences, personal traits, sociodemographic factors, and learning experiences are known to be important [ 7 ]. A change has taken place in recent decades among medical students to follow specialties that offer greater control over lifestyle, and the less flexible lifestyle of surgical specialties has become an important reason for viewing this field as less attractive [ 7 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, interests and preferences, personal traits, sociodemographic factors, and learning experiences are known to be important [ 7 ]. A change has taken place in recent decades among medical students to follow specialties that offer greater control over lifestyle, and the less flexible lifestyle of surgical specialties has become an important reason for viewing this field as less attractive [ 7 9 10 ]. A 2013 Korean study found that income, lower workload, and intellectual stimulation were the most influential factors [ 21 ], while a 2017 Canadian study rated job satisfaction and lifestyle following training as the highest [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from a variety of countries explored the criteria medical students use when selecting a career specialty. These studies found that influencers (clerkship experiences, mentors, junior and senior physicians), lifestyle (work–life balance, control over life style), personal attributes (personality, interests, gender, marital status), socioeconomic considerations (future earnings, loan repayments) and perceptions of the various specialties are important criteria when choosing a specialty and a residency program [ 5 8 ]. The leading criteria in many studies were the ability to have a controllable lifestyle and finding the specialty interesting and challenging.…”
Section: Introductionmentioning
confidence: 99%